Analysis of the Implementation of the Indonesian National Qualifications Framework Oriented Curriculum in the Mathematics Education Program of Universitas Negeri Medan - Yuliani Aruan; Edi Syahputra; Edy Surya (BIRCU, 2021)
This study aims to describe: 1) the implementation of the curriculum oriented to the Indonesian National Qualifications Framework (KKNI), 2) student responses to the six tasks required in the KKNI curriculum, 3) the quality of student performance and achievement with the implementation of the KKNI curriculum. This research is a descriptive qualitative research which aims to describe the implementation of the curriculum oriented to the Indonesian National Qualifications Framework (KKNI). Subjek in this study were undergraduate students-1 in the first semester, three, and five mathematics education of UNIMED. The subjects who were subjected to in-depth interviews were randomly selected six students. Data obtained from the distribution of questionnaires and observations of the lecture process and in-depth interviews. The object of this research is the implementation of the KKNI curriculum, student responses, performance, and achievement oriented to the Indonesian National Qualifications Framework (KKNI). Based on data analysis, it is found that: 1) The implementation of the Indonesian National Qualifications Framework (KKNI) has not been carried out optimally or well in the mathematics education lecture process, 2) Students have a positive response to the application of the Indonesian National Qualifications Framework (KKNI), 3) Performance Quality is quite good in the application of the Indonesian National Qualifications Framework (KKNI), 4) Students' learning achievement is quite low in the application of the Indonesian National Qualifications Framework (KKNI).